ANALISIS NEGOSIASI DALAM PROSES AKUISISI LUCASFILM LTD. OLEH THE WALT DISNEY COMPANY - Absherina Zahira Sofyan; Cecep Safaatul Barkah; Nurillah Jamil Achmawati Novel (POLITEKNIK LP3I JAKARTA, 2022)
Business acquisition is one of the steps taken by the company in its business expansion strategy, as did by the Walt Disney Company by acquiring production company, Lucasfilm Ltd. In the business acquisition process, negotiation is an inherent thing and becomes one of the stages that must be carried out during the process. Therefore, good negotiation techniques and strategies need to be applied to get a profitable agreement. This study was conducted to determine the negotiation process and the strategy used by Disney in the Lucasfilm acquisition process. The method used in this research is literature study with sources derived from books, scientific articles, reports, and media publications. The results of this study indicate that in the Lucasfilm acquisition process an integrative negotiation approach was applied. Disney applies a negotiation strategy, namely by fostering trust from the opposing party and providing mutual benefits. From the negotiations, an agreement was obtained that provided value for both parties and can be concluded as mutually beneficial.Key words: Acquisition, Negotiation, Integrative Negotiation